John Kenneth Mackenzie and the Dawn of Modern Healthcare in Tianjin: Insights from the “Newly Established Sanatorium Stele” in the Tianjin Museum Collection - GUO Hui (Journal of Research for Christianity in China (JRCC), 2025)
The “Newly Established Sanatorium Stele” housed in the Tianjin Museum documents the medical practice and establishment of the “Governor’s Hospital” by John Kenneth Mackenzie, a missionary of the London Missionary Society in Tianjin. It highlights his significant contributions to modern medical care and health education in Tianjin. Notably, after the first group of children studying in the United States returned home, some enrolled in the newly established “Medical School Affiliated with the Governor’s Hospital” at John Kenneth Mackenzie’s initiative, marking the beginning of Western medical education in China. This article will examine how medical missionaries from the London Missionary Society, represented by Morgan, influenced China’s upper echelons—including Li Hongzhang—to foster the inception and continuous development of modern medical and public health services in Tianjin. This analysis will draw upon relevant artifacts and archival materials preserved in the Tianjin Museum.